Use of pruning in the agricultural management of Jatropha curcas (jatropha) for the plant flower development, in Costa Rica - Moreira-González, Ileana (2019)
The species Jatropha curcas (jatropha) is characteristic of the Mesoamerican region, with its center of origin found in Mexico. It has been adapted for its use as hedge rows and also exploited, based on traditional knowledge for medicinal applications. Currently, it is classified as a valuable species for the production of oils; for biofuels or as paint diluents. In Costa Rica, since 2005, studies have been performed to achieve the positive domestication for the use of this species as an agro-energetic crop along with another food crop. However, the crop management processes are still very recent and it is required to deepen in this subject to obtain a crop of a high economic value. At the Estación Fabio Baudrit, a crop was established, using seeds from the Comayagua variety and an assay was established, in which a strict assessment was performed to random blocks, of the plants length in order to execute the first prune at 40 cm. Later, the blocks were also tracked, to evaluate the branches until the flowering and harvesting stages. The yield of green fruits behaved similarly to the inflorescence and the female flower production. The pruned plants did not present a significant difference in terms of fruit yield for the first year; but in the second year, they exceeded the production of the unpruned plants.